Sistem Pendukung Keputusan Pemilihan Guru Terbaik Dengan Menerapkan Metode WASPAS Dan Pembobotan Menggunakan Metode ROC Pada Sekolah Menengah Pertama (SMP) - Supiya Supiya; Muhammad Syahrizal; Sarwandi Sarwandi (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
State Junior High School 1 Datuk Fifty is a public school located at Simpang Dolok Batu Bara. So far, the selection of the best teachers is still experiencing problems, namely the frequent occurrence of nepotism. In addition, the selection of the best teachers is still done manually. So that errors often occur in the assessment of the selection of the best teacher. Not only that, even the school still chooses only the closest people who will be the best teachers. So that in the assessment of the best teacher, it is necessary to do how to teach students well, improve the quality of teaching work in the room and have the motivation to become the best teacher. So to overcome these problems a decision support system is needed in selecting the best teachers by applying the Weighted Aggregated Sum Product Assessment (WASPAS) method in the ranking process, and the Rank Order Centroid (ROC) method to produce weight values. According to the results of the ranking which was carried out using the Weighted Aggregated Sum Product Assessment (WASPAS) method, the one who obtained the highest score would be selected as the best teacher at Datuk Fifty Public Middle School (SMP) 1.